Laboratory diagnostic markers in assessing the state of patients with osteoarthrosis, who need prosthetic arthroplasty of large joints (a review of literature) - Filipenko, Volodymyr; Leontyeva, Frieda; Morozenko, Dmytro; Korzh, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The paper considers the use of hemostasis, biochemical and immunological tests in patients with osteoarthritis of the large joints (knee, hip) during replacement. Given existing in the modern laboratory diagnosis markers, which is used on patients to evaluate the health status before and after joint replacement.